Overview of Removal Methods for Co2 and Other Greenhouse Gas and Details of the Method Using Nonthermal Plasma - Marcela Morvová; Morva Imrich; Mário Janda (The Minerals, Metals and Materials Society, 2010)
"The possibilities of greenhouse gas mitigation using various methods are brought out. The special case of utilization of mixture of CO2 with other greenhouse gases in a synergetic way inside non-thermal plasma based system is described in detail.Measurements on pilot system comprising pyrolysis chamber as alternative energy system (production of hydrogen and liquid tar) were made for various biomass and waste as the input material. The exhaust from this system was treated with non-thermal plasma gap suitable for up to 650Nm3/hour of exhaust gas flow. Condensable portion of exhaust is liquefied in distillation unit; produced hydrogen is stored on-line inside nano sized carbon of our own production.The CO2 removal efficiency varies depending on exhaust composition between 45 to 98%. Other oxides as CO, NOx, SOx and several hydrocarbons and VOC are also removed. The main product connected with CO2 removal is a solid powder of proteinoid nature. There exist strong probability, that precursor of the origin of life on the Earth from primary atmosphere were formed in the similar way as it is present in the electric discharge system used. Our system is equipped with on-line as well as ex-post analysis of all forms of products. We have also developed a system for recuperation of all forms of produced heat. It is stored inside as latent heat of waxes.IntroductionNatural greenhouse effect on the Earth is caused mainly by water vapour with the average absolute concentration about 4%. Other gases able to absorb long-wave radiation and thus this causing greenhouse effect are CO2, CH4, N2O, halocarbons and as precursors ozone and NOX. Some of them we produce and introduce into atmosphere in large quantities during production of energy and in transport. This factor leads to permanent increase of average temperature of air, sea and oceans, so called global warming.Nowadays large amount of data exists showing that the temperature of Earth in the last 150 years has been continually increasing. It represents about 03°C per ten years and the most of climatologist believe, that the increased concentration of greenhouse gases in the atmosphere is responsible for this effect.The most important greenhouse gas is carbon dioxide CO2. Majority of CO2 emissions comes from electric power stations working with fossil fuels, cars and industry. Burning of fossil fuels contribute up to 80% to world wide anthropogenetic emissions of CO2."